Communication training is inadequate: the role of deception, non-verbal communication, and cultural proficiency. Issue 1 (1st January 2020) - Baugh, Aaron D.; Vanderbilt, Allison A.; Baugh, Reginald F.
ABSTRACT: In this commentary, we argue that the limited experiential exposure of medical students to different cultures makes the instruction devoted to communication skills inadequate. The relationship of these dynamics to honesty in clinical encounters is explored. Absent significant experiential exposure to differing group cultures to counter the natural tendency to favor one's own, discrimination prevails. Knowledge or awareness of cultural differences does not necessarily equate to communication proficiency. Critically, interactions based on lived experience offer a deeper knowledge and understanding of culturally meaningful nuances than that imparted through other formats. Medical students' lack of experiential exposure to different cultures results in communication miscues. When the stakes are high, people detect those miscues diminishing trust in the doctor-patient relationship. Greater experiential cultural exposure will enhance the facility and use of culturally specific communication cues. At its core, the requisite transformation will require medical students to adapt to other cultures and greater representation by marginalized and stigmatized populations not only among the studentry but staff and faculty. The time is now to ensure that the physicians we produce can care for all Americans. What cannot be taught must be identified by the selection process. Competence with half the population is a failure for American medicine.